Pyoderma Gangrenosum among Patients with Inflammatory Bowel Disease: A Descriptive Cohort Study. Issue 2 (March 2015) - Weizman, Adam V.; Huang, Brian; Targan, Stephan; Dubinsky, Marla; Fleshner, Phillip; Kaur, Manreet; Ippoliti, Andrew; Panikkath, Deepa; Vasiliauskas, Eric; Shih, David; Mcgovern, Dermot P.B.; Melmed, Gil Y.
Background: Pyoderma gangrenosum (PG) is a severe extraintestinal manifestation of inflammatory bowel disease (IBD). Objective: To better characterize PG features and management among an IBD cohort. Methods: Subjects with PG were identified using a large database at a tertiary center. Patient demographics and clinical characteristics were summarized using descriptive statistics. Results: Eighty patients with an episode(s) of PG were identified, yielding an overall prevalence of 1.9%. Overall, 93% of patients with PG had some degree of colonic inflammation. Thirty-one (39%) patients required hospitalization for PG. Underlying bowel disease was active at the time of PG episode(s) in 52 (65%) patients. The PG location was variable, with the lower extremity being the most common. Most patients (71.3%) required multiple therapies to achieve PG healing. Conclusions: We describe one of the largest case series of PG among patients with IBD. The variety of treatment strategies used highlights the lack of clear guidelines in managing this complex group of patients.